Effects of the Transcendental Meditation Program on Substance Use among University Students - David A. F. Haaga; Sarina Grosswald; Carolyn Gaylord-King; Maxwell Rainforth; Melissa Tanner; Fred Travis; Sanford Nidich; Robert H. Schneider (Cardiology Research and Practice)
A randomized wait-list controlled trial (𝑁=295 university students) of the effects of the Transcendental Meditation program was conducted in an urban setting. Substance use was assessed by self-report at baseline and 3 months later. For smoking and illicit drug use, there were no significant differences between conditions. For alcohol use, sex X intervention condition interactions were significant; TM instruction lowered drinking rates among male but not female students. TM instruction could play a valuable role in reducing alcohol use among male university students. Limitations are noted, along with suggestions for further research.